Norma dan Negosiasi dalam Fandom Plave Indonesia di X - Kencana, Sekar Maryam; Rahayu, Lina Meilinawati; Prabasmoro, Tisna (Jurnal Sosioteknologi, 2025)
In virtual idol fandoms, fans often follow shared norms that shape how they interact with one another. This research draws on fandom, norms, and negotiation theories to explore how such norms emerge and are negotiated within the Plli fandom on social media X, focusing on the figure of “Terra Plave” as the controlling presence behind Plave’s virtual idol avatar. Based on data from phenomenological interviews with four Indonesian fans, the study identifies two central aspects of these norms: the types of accounts fans use and their responses to provocative posts and doxxing. The findings suggest that the norms surrounding Terra Plave reflect an ongoing process of negotiation among fans, aimed at resolving internal conflicts triggered by official statements from Plave’s label.